Curriculum 5.0: Reimagining Education Management with Augmented Reality and Learner-Centric Design - Loso Judijanto; Arkam Lahiya; Seno Lamsir (PT. Sinergi Bersahaja Sejahtera, 2025)
Background. The transition toward Curriculum 5.0 reflects a paradigm shift in education management, where emerging technologies such as Augmented Reality (AR) and learner-centric pedagogies are integrated to foster personalized, immersive, and competency-driven learning experiences. In this context, AR is not merely a technological tool but a transformative medium that enhances engagement, contextual understanding, and collaboration, while learner-centric design ensures that educational processes are tailored to individual needs, preferences, and learning pathways. Purpose. This quantitative study aimed to investigate the influence of Augmented Reality-based instructional environments and learner-centric design strategies on the perceived effectiveness of education management within the Curriculum 5.0 framework. Specifically, it examined whether these perceptions differ according to educators’ digital competence, teaching experience, field of expertise, and openness to technology adoption. Method. The study involved 312 educators from diverse educational institutions who had experience integrating AR into curriculum delivery. Data were collected through a structured questionnaire measuring perceptions of AR’s pedagogical value, the quality of learner-centric design, and overall education management effectiveness. The responses were analyzed using statistical methods, including descriptive analysis, ANOVA, and multiple regression, to identify relationships and differences across demographic and professional variables. Results. The findings indicate that both AR integration and learner-centric design strategies have a significant positive impact on the perceived effectiveness of education management. Educators with higher digital competence and openness to innovation reported stronger alignment between AR-enhanced instruction and the goals of Curriculum 5.0. Conclusion. This study provides empirical support for the integration of AR and learner-centric design in realizing the vision of Curriculum 5.0. By combining immersive technology with personalized learning approaches, educational institutions can create adaptable, engaging, and future-ready learning ecosystems.